Relationship between changes in haemoglobin mass and maximal oxygen uptake after hypoxic exposure - Saunders, P. U.; Garvican-Lewis, L. A.; Schmidt, W. F; Gore, C. J. (British Journal of Sports Medicine, 2013)
Background: Endurance athletes have been using altitude training for decades to improve near sea-level performance. The predominant mechanism is thought to be accelerated erythropoiesis increasing haemoglobin mass (Hbmass) resulting in a greater maximal oxygen uptake (O2max). Not all studies have shown a proportionate increase in O2max as a result of increased Hbmass. The aim of this study was to determine the relationship between the two parameters in a large group of endurance athletes after altitude training.Methods 145 elite endurance athletes (94 male and 51 female) who participated in various altitude studies as altitude or control participants were used for the analysis. Participants performed Hbmass and O2max testing before and after intervention.Results For the pooled data, the correlation between per cent change in Hbmass and per cent change in O2max was significant (p<0.0001, r2=0.15), with a slope (95% CI) of 0.48 (0.30 to 0.67) intercept free to vary and 0.62 (0.46 to 0.77) when constrained through the origin. When separated, the correlations were significant for the altitude and control groups, with the correlation being stronger for the altitude group (slope of 0.57 to 0.72).Conclusions With high statistical power, we conclude that altitude training of endurance athletes will result in an increase in O2max of more than half the magnitude of the increase in Hbmass, which supports the use of altitude training by athletes. But race performance is not perfectly related to relative O2max, and other non-haematological factors altered from altitude training, such as running economy and lactate threshold, may also be beneficial to performance.